Estimating an optimal threshold value for foreign investment in Malaysia / NoorZahirah Mohd Sidek and Mahadzir Ismail - Mohd Sidek, NoorZahirah; Ismail, Mahadzir (2012)
The major thrusts of the 10th Malaysia Plan are geared towards transforming Malaysia into a high income nation. Higher income per capita can only be achieved with higher growth of GDP. In the past, GDP growth in Malaysia is supported by the influx of foreign direct investment which fuels the export-oriented industries. Domestic investment in terms of infrastructure and human capital development further enhance the influx of foreign direct investment into Malaysia.